Assessment of Phytochemical Constituents of Stem Bark Extract of Albizia adianthifolia and its in-vivo Antiplasmodial Activity on Mice infested with Plasmodium berghei - I. O. Okoro (Journal of Applied Sciences and Environmental Management, 2022)
Malaria, one of the most debilitating diseases, has a huge impact on large populations in tropical and subtropical areas. Albizia adianthifolia is a perennial evergreen that thrives in moist tropical forest areas. This study intended to assess the phytochemical constituents of stem bark extract of Albizia adianthifolia and its in-vivo antiplasmodial activity on mice infested with Plasmodium berghei. The plant's antimalarial effects at 100, 200 and 400 mg/kg b. wt. dosages against the chloroquine-sensitive strain, Plasmodium berghei were examined using the 4-day suppressive and rane's, tests. In this experiment, 25 mice were classed into five groups (3 treatment and 2 control groups, each with five mice). Parasitaemia, existence time, body mass, and packed cell volume were used to assess the antiplasmodial activity of the extracts. In the 4-day suppression investigation, all doses of the crude extract significantly (P < 0.05) reduced parasitemia, compared to the negative control, with the strongest suppressive effect of 59.93% obtained at dose 400 mg/kg b. wt. Similarly, the Rane's test revealed significant (P <0.05) curative effect (69.03%) at the highest dose, when compared to the untreated control. According to the findings of the phytochemical screening, the extract contains alkaloids, flavonoids, anthraquinones, tannins, triterpenes, sterols, and saponins. Also, treatment of P. berghei-infected mice with the crude extract in both suppressive and curative tests considerably extended the mean survival time relative to the negative control, notably at the highest dose (400 mg/ kg b. wt.). Thus, this study shows that Albizia adianthifolia stem bark extract possesses antiplasmodial efficacy against P. berghei-infected mice, which may be due to its phyto-constituents.